Parent–Child Time Together: The Role of Interactive Technology With Adolescent and Young Adult Children. (October 2019) - Vaterlaus, J. Mitchell; Beckert, Troy E.; Schmitt-Wilson, Sarah
Presently, there is a lack of consensus about whether interactive technology enhances or restricts the quality and quantity of shared time between parents and their children. The purposes of this exploratory study were to identify parent and adolescent/young adult perceptions of time spent together and to investigate ways in which the use of technology is related to that time. Using a purposive sample, 766 youth (high school and early college) and their parents ( n = 735) responded to questions about their interactive time spent together. Results indicated that parents and their adolescent/young adult children distinguished between parent–child quality and parent–child quantity time. Participant perceptions of both quality and quantity parent–child time were explored in relation to parent–child computer-mediated communication via text messaging, telephone calls, social networking, video chat, and e-mail. The type of interactive technology was related to participant perceptions of parent–child quality time more than the quantity of time.